Brand Identity and Information on Instagram Social Media @Course Net: Identitas Merek dan Informasi di Media Sosial Instagram @Course Net - Hastowo, Kiki Widyasari; Sinduwiatmo, Kukuh (Universitas Muhammadiyah Sidoarjo, 2025)
Interaction with technological and information developments builds communication efficiency. New media in the form of social media Instagram has become a form of mediation for the community's needs in conveying and receiving news or information. The era of industrial revolution 4.0 is building media interests which are accompanied by business and computer movements simultaneously. The Instagram account @course_net is one of many accounts that can provide access to all the interests of the 4.0 revolution era in one. Social media-based information with content related to IT and computers is packaged attractively through an information formation system with a visual communication style according to its characteristics so that it can build a new culture within the scope of Instagram accounts. The culture that is formed can be accepted by users with the ease of Instagram features for exchanging opinions and experiences. This research aims to identify the process of forming a brand identity and information system contained in the communication that occurs in the content on the @course_net Instagram account, and researchers want to know how the elements of visual communication are contained in the content. Researchers use the focus of netnography theory to analyze interactions that occur within accounts in any form. The culture of interaction on the Course Net account is part of an interaction that respects each other and accepts opinions across community circles. So that every member dares to express their opinions and arguments without any restrictions. Highlights: Communication Efficiency: @course_net uses Instagram to share IT content aligned with the Industry 4.0 era. Visual Identity: Content is attractively packaged with a distinct visual style to build brand identity. Cultural Interaction: The account fosters an inclusive culture that encourages open and respectful discussion. Keywords: Brand Identity, Social Media, Netnography, Instagram